THE PRINCIPLE OF PERMISSIBILITY AND NORMATIVE CONSTRAINTS IN CONTEMPORARY FIQH MUAMALAH: Asas Kebolehan dan Batasan Normatif dalam Fiqh Muamalah Kontemporer - Mohammad Irfan; R. Edi Komarudin; Asep Ahmad Fathurahman (Tunas Harapan Ummat Foundation, 2026)
Contemporary fiqh muamalah represents a methodological extension of classical fiqh muamalah aimed at preserving the relevance of Islamic law in the face of modern social and economic transformations. Theoretically, contemporary fiqh muamalah functions as a normative system that integrates the primary sources of Islamic law namely the Qur’an, sunnah, ijmaʿ, and qiyas with evolving social, economic, and technological realities. This study seeks to examine the theoretical framework of contemporary fiqh muamalah, particularly the principle of permissibility and its normative constraints, in addressing modern transactional practices. Employing a qualitative approach through library research with descriptive-argumentative analysis, this study finds that the principle of permissibility (al-aṣl fī al-muʿāmalāt al-ibāḥah) constitutes the foundational maxim for assessing contemporary transactions, while remaining inherently bounded by axiomatic normative principles, including the prohibition of riba, gharar, tadlis, maysir, as well as unlawful products and invalid contracts. In relation to modern economic instruments such as cryptocurrency and venture capital, contemporary fiqh muamalah necessitates an evaluative and contextual approach rather than generalized legal judgments. Cryptocurrency must be assessed based on its function, mechanism, and intended use, whereas venture capital may be deemed compatible with Islamic legal principles when structured within equitable and transparent partnership-based contracts. This study recommends further research that incorporates empirical and interdisciplinary approaches to examine the practical application of contemporary fiqh muamalah principles in digital finance and modern investment models, thereby strengthening an adaptive and maslahah-oriented formulation of Islamic law.